The upper thermal tolerance for a Texas population of the hairy maggot blow fly Chrysomya rufifacies Macquart (Diptera: Calliphoridae). (23rd June 2020) - Rusch, Travis W.; Faris, Ashleigh M.; Beebe, Lauren E. J.; Tomberlin, Jeffery K.; Tarone, Aaron M.
Abstract : The hairy maggot blow fly ( Chrysomya rufifacies : Macquart) is an invasive necrophagous fly found throughout the continental United States. Chrysomya rufifacies is of medical/veterinary, forensic, and ecological importance due to its ability to cause myiasis, colonise human remains, and displace native Diptera. However, little is known about their upper thermal tolerance, which could be used to better predict their invasion potential. We investigated the upper thermal tolerance of C. rufifacies exposed to different temperatures (20–45 °C), times (1–6 h), and nutrients (no food or water, water only, or a food‐water mixture) for both sexes and two age ranges (young = 6–8 days post pupal emergence; old = 9–11 days post pupal emergence). As temperature or duration increased, the probability of knockdown increased (0–100% at 20 and 45 °C and from 41 to 75% at 1 and 6 h), while the probability of survival decreased (99–2% at 20 and 45 °C and from 75 to 28% at 1 and 6 h). The availability of nutrients increased thermal tolerance at moderate temperatures (40 and 42 °C). Female flies were more thermally tolerant than males (probability of knockdown = 49% vs 58%; probability of survival = 58% vs 46%). Thermal tolerance did not differ by age. These data reveal details about the upper thermal tolerance for a single population of C. rufifacies, and suggest that environmental and organismal factors ought to be considered in order to make meaningful predictions about the invasion potential of C. rufifacies in North America. Abstract : The upper thermal tolerance of Chrysomya rufifacies was impacted by both absolute temperature and exposure duration. The availability of nutrients enhanced the upper thermal tolerance of C. rufifacies . Invasive C. rufifacies is a relative thermal specialist compared to native Cochliomyia macellaria, which may partially explain why C. rufifacies has not successfully eliminated C. macellaria from North America.